Patterns of entry and exit in the deregulated German interurban bus industry - Niklas S. Dürr; Kai Hüschelrath (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
We study patterns of entry and exit in the German interurban bus industry in the first three years after its deregulation in January 2013. Using a comprehensive data set of all firm and route entries and exits, we find that the industry grew much quicker than originally expected - with particularly a few new entrants being most successful in quickly extending their route networks from regional to national coverage. Although the clear majority of routes is operated on a monopoly basis, competition does play a key role on routes with a sufficiently large base of (potential) customers. From a spatial perspective, three years after deregulation, the entire interurban bus network connects 60 percent of all 644 larger German cities - with the intensity of entry being dependent on the number of inhabitants, average income, the share of under 24 years old and the presence of intermodal competition by intercity railway services.
urn:nbn:de:bsz:180-madoc-436093
Keywords: L11; L41; L43; L92; K21; K23; 330; deregulation; interurban bus services; entry; exit; competition